Microempreendedor individual: percepção sobre sua formalização - Stooc, Marcia Bonifácio (2018)
The Individual Microentrepreneur Program is an alternative for the reduction of entrepreneurs who work informally, however, it is important to identify if the offered benefits are attractive for this working class. Thus, the objective of this work is to verify the perception of the Individual Microentrepreneurs that participated in the “Bom Negócio Paraná” Program, regarding the benefits generated by the formalization and improvement in the results of their business. This research is classified into quantitative nature, having as sample 190 Microentrepreneurs that participated in the “Bom Negócio Paraná” Program. To meet this research’s goals, a questionnaire in a Likert-type scale was applied, divided in three stages, which the first one consists in charting a profile of the respondents, the second one, identifying the benefits of the Individual Microentrepreneur Program, and the third one, identifying the results of these enterprises after the formalization as an Individual Microentrepreneur. A descriptive analysis of the data was made to chart the profile of the research’s respondents. To identify the benefits and the results after the formalization, a descriptive and frequency analysis were made. To develop a comparative analysis of the benefits and results, the non-parametrical Kruskal-Wallis test was applied between the Individual Microentrepreneurs of ten centers of the “Bom Negócio Paraná” Program, to test the hypothesis that they present the same distribution between the variables, and a peerreview was made to detect which centers presents itself differently than the others. As result of the research, it was identified that the majority of the respondents are male and that they are between 31 and 40 years. They opened their enterprises for opportunity and worked as legally registered workers before the formalization. Among the most evaluated benefits from the respondents, there was the possibility of selling to other companies for the fact that they can emit invoice. The Microentrepreneurs as the main improvements identified client’s satisfaction and an increase in production and services after the formalization. As for the negative points after the formalization, only being able to hire one employee and the revenue limit are the main drawbacks. After the application of the Kruskal-Wallis method, it was possible to identify that there was a variation between both the benefits and the results, in which the Individual Microentrepreneurs of centers of Cascavel and Guarapuava presented lower average scores more often in their answers, providing differences between the centers categories.